Students’ Perception of English Online Learning During Covid-19 Pandemic - husnayaini, ihda; Salsabila, Dzihan (English Education Department, 2022)
This study was aimed to obtain the students’ perception towards English online learning during Covid-19 pandemic in Indonesia, especially in a private junior high school in Bangka province. The research method used in this study was a descriptive research design with a quantitative approach. The data were obtained with an interview, questionnaire, and documentation. The subject of this study were 34 members of eighth-grade students in Dendang village. especially in English subject. Based on the analysis of the data did by the researcher, the researcher found that learning English through online learning during the Covid-19 pandemic got positive perceptions in the aspect of the dimension of teaching material with 16 respondents strongly agreed at the highest percentage of 47.1%, the dimension of atmosphere/environment with 17 respondents strongly agreed at the highest percentage of 50%, the students’ interaction with 18 respondents strongly agreed at the highest percentage of 53%, and the benefits of learning English through online learning with 21 respondents strongly agreed at the highest percentage of 61.77%. Thus, it concluded that the students perceived that they can adjust the learning process to all aspects contained in the online learning process.